Spatio-temporal patterns of high summer ozone events in the Madrid Basin, Central Spain. (July 2018) - Reche, C.; Moreno, T.; Amato, F.; Pandolfi, M.; Pérez, J.; de la Paz, D.; Diaz, E.; Gómez-Moreno, F.J.; Pujadas, M.; Artíñano, B.; Reina, F.; Orio, A.; et al.
Abstract: Complex spatial and temporal patterns of ground-level O3 and NO2 concentrations have been revealed across an important southern European O3 exceedance area (Madrid Basin, central Spain). Data were obtained from 102 diffusion tube sites and 49 monitoring stations (25 urban/suburban, 12 urban/suburban-traffic, 7 remote, 3 rural, 2 urban-industrial) located through a wide area inside and beyond the city. This new, high-density database confirms that current locations of monitoring stations in the Madrid networks are well positioned to record representative levels of O3 across the area. Two air quality monitoring stations were identified as reference measurement points, based on their lower O3 and NO2 concentrations, and used as a proxy for regional and hemispheric background levels. Although a main regional contribution was evidenced, emissions of local precursors within the Madrid urban plume play a key role in the generation of O3 exceedances, which are higher and occur earlier near the city than at rural sites, where the effect of NO titration is lower. Despite the fact that weekend emissions of O3 precursors in Madrid are typically lower than on weekdays, mainly due to fewer road traffic emissions, there is little difference in average values of weekday and weekend O3 . However, more subtle "weekend effect" differences are revealed by probability density analysis, with high O3 and low NO2 at the highest temperature range (30-35° C) at weekends reflecting lower NO titration. This analysis highlights the importance of NO timing with respect to the photochemical activity timing. The complexity of these O3 pollution patterns in and around the city is dependent on an ever-changing interplay between weather conditions, emission sources, and the timescale required for pollutant transport, chemical processing and recirculation in an evolving contaminated airmass. Highlights: O3 and NO2 assessed in the Madrid Basin covering 151 sampling points (49 monitoring stations +102 diffusion tubes). Monitoring stations of the Madrid network proved to report realistic and representative O3 levels. Two monitoring stations identified as a proxy for external regional O3 contribution. A dependence of O3 exceedances on the Madrid urban pollution plume was evidenced. A clear O3 "weekend effect" was not observed under high insolation conditions.